The complete mitochondrial genome of Batrachuperus sp. 2 (Caudata: Hynobiidae) - Zhang, Pizhu (Mitochondrial DNA B Resour, 2020)
We describe the mitochondrial genome sequence of a mountain salamander, Batrachuperus sp.2 (Hynobiidae). The mitogenome was extracted and assembled from a large genome by next-generation sequencing. The mitochondrial genome sequences were 16,394 bp in size with 37 genes including 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a non-coding control region (D-loop). The overall base composition of Batrachuperus sp.2 is 34.1% for A, 19.3% for C, 13.5% for G, 33.1% for T, and 32.8% for GC content. The phylogenetic tree was constructed based on 13 protein-coding genes of Batrachuperus sp.2 and 6 closely related species by RAxML.